Educational paradigm for the future - Apriyani, Helina (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Education is the basis for human civilization. Education is able to bring technological developments and changes in thinking power for the better. Humans must be able to make a significant contribution towards the progress of the times. Able to create superior quality Human Resources. This research uses qualitative methods and literature studies in searching for data and reference sources. The aim of writing this journal is to provide information about future educational paradigms that will adapt to the environment, technological developments and social changes and ensure that education is affordable. The results obtained from this research are that there is a need for collaboration between power and policy holders and the community. The government and society can work together to create education that is relevant to current developments and capable of creating superior and highly competitive human resources. The educational paradigm illustrates that education is dynamic, constantly changing and developing. Therefore, quality and superior human resources are very necessary. Teaching staff must also have good quality qualifications and competencies in providing teaching to students. This research finds that future educational paradigms must be more flexible, student-centered, and focused on developing 21st century skills such as critical thinking, creativity, and collaboration abilities. The integration of technology in the learning process is also an important aspect to achieve this goal.